Peran Akreditasi Dalam Peningkatan Mutu Lulusan Dalam Dunia Pendidikan - Aminudin Busra; Rizadiliyawati Rizadiliyawati; Dahrani Dahrani; Sohiron Sohiron (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Accreditation plays a crucial role in enhancing the quality of education and graduates by ensuring that educational institutions meet established standards. As a quality assurance instrument, accreditation encourages continuous improvement in curriculum, educator competency, facilities, and quality management. Its impact is evident in producing graduates who are competent, competitive, and trusted by the workforce. However, the implementation of accreditation faces challenges such as disparities in education quality across regions, difficulties in adapting to technological changes, and potential issues with transparency in assessments. To enhance its effectiveness, collaboration between accreditation bodies, educational institutions, the government, and the industrial sector is necessary to establish relevant standards and promote inclusivity. By strategically addressing challenges and utilizing opportunities, accreditation can become a driving force in creating a high-quality education system, aligned with labor market demands, and capable of producing graduates who are well-prepared to contribute to society